Organic Manure in Conservation Agriculture: Perception, Reality and Interpretation - Bera, Sreemoyee; Acharya, S. K.; Kumar, Prabhat; Chatterjee, Riti; Mondal, Kabita; Haque, Monirul (Indian Journal of Extension Education, 2022)
The excessive reliance on chemical fertilizers and the negligence shown to the conservation and use of organic manures (OM) have led to the exhaustion of organic carbon level, soil moisture level, and retention of microorganism population in the soil. The present study reveals that the farmers merely have any perception or they are not technically aware of the importance of the application of OM into their farming for the restoration of ecological resilience. Elucidating the factors, impacts, and perceptions of farmers, fifty respondents have been selected from Dalilpur and Kastodanga village of Nadia district by systematic random sampling for the study. The responses are collected through a structured interview schedule.The study envisaged that the livestock count, size of homestead land, size of landholding, production of organic manure, education variables have been found to exert strong and determining contribution to the application of organic manure. The socialization of proper cognitive adoption of organic manure among the farmers for the restoration of ecological resilience and popularization of resource-saving agricultural crop production is the need of the hour.
Keywords: Conservation agriculture; Ecological resilience; Organic carbon level; Organic manure; Perception